Exploring Writing Challenges In Research Article Introductions Across Diverse Scientific Disciplines Within Educational Settings - Mouad Lahmer; Abderrahim Benmachiche (The Journal of Studies in Language, Culture and Society, 2024)
This study examines challenges faced by authors in crafting impactful introductions for research articles across diverse scientific fields within educational settings. Analyzing 103 research articles written by non-native English speakers, we conducted a detailed error analysis, assessed readability scores, and explored correlations to identify specific writing difficulties unique to this critical section. While prevalent grammatical errors, such as article usage and subject-verb agreement, were identified, readability scores suggested a moderate to challenging level of comprehension. Significant variability in text complexity and writing styles was observed, emphasizing the need for tailored guidance to address individual author needs. Positive correlations were found between factors like article usage and grammar accuracy, while negative correlations emerged between aspects like paragraph length and sentence length. These findings contribute significantly to understanding writing challenges in research introductions, providing valuable insights for authors and educators. By improving the clarity and impact of research introductions, this study has potential applications in enhancing knowledge dissemination and supporting evidence-based decision-making across various sectors.